The Effect of Direct and Indirect Taxes on Economic Growth in Developed Countries - Shaqiri, Valentina; Elshani, Alban; Ahmeti, Skender (Ekonomika, 2024)
This paper examines how the economic growth in advanced countries is affected by various types of tax revenue. Ten developed countries were chosen based on the Human Development Index, and data from 1995 to 2020 were examined using the feasible generalized least squares method. A total of 260 observations spanning 26 years were available for analysis. The purpose of this paper is to investigate the influence of direct and indirect taxes on economic growth in selected developed countries. According to our results, the growth of these countries was positively influenced by corporate income taxes and taxation on specific goods and services. However, there are adverse impacts from taxes on personal income, contributions to social security, and a tax on value-added. For a beneficial impact on these nations’ growth, we suggest policymakers concentrate on taxes on corporations and specific services and goods. Furthermore, it is important to consider the adverse impacts of personal taxation and value-added taxation on growth.